Experimental Study on Seismic Performance of Prefabricated Utility Tunnel. (27th October 2019) - Duan, Xu; Dong, Qi; Ye, Wanjun
Abstract : Utility tunnel is a kind of underground tunnel structure that carries more than two types of public utility lines, and the utility tunnels built by the prefabricated method have been adopted in many modern cities due to their easy maintenance and environmental protection capabilities. However, knowledge about the seismic performance of the prefabricated utility tunnel and pipelines inside is quite limited. In this paper, a prefabricated utility tunnel newly built in Xi'an, China, is taken as the prototype; a series of shaking table tests are conducted to investigate the seismic performance of the prefabricated utility tunnel in loess foundation, using El Centro earthquake wave as the input loading. Details of the experimental setup focus on the design of the soil container, scaled model (1 : 10), sensor arrangement, and test cases. Dynamic responses including evaluation of boundary effect, the amplification factor of the ground and structure, distribution of soil pressure, characteristics of predominant frequencies, and the damage phenomena are analyzed. Dynamic strain obtained by Fiber Bragg Grating sensors releases the critical positions of the prefabricated utility tunnel during the earthquake. Moreover, the dynamic responses of the pipelines contained in the utility tunnel are also analyzed. From aforementioned results, the seismic performance of the prefabricated utility tunnel has been revealed. The results will provide a reference for the seismic design of prefabricated utility tunnels.